Altruism and Workers' Remittances : Evidence from Selected Countries in the Middle East and Central Asia - Bouhga-Hagbe, Jacques (Washington, D.C. : International Monetary Fund, 2006)
Workers' remittances have been playing an increasingly important role in the balance of payments of many countries and can significantly contribute to the strength of their external positions. Assessing the likely stability of remittance flows could be a valuable input to the analysis of their external vulnerabilities. This paper argues that "altruism," as a motive to send money home, would contribute to the stability of these flows. Using a simple framework that relates workers' remittances to agricultural GDP, which is used as an indicator of economic "hardship" in the home country, evidence suggests that altruism could have played an important role in the flow of remittances to Egypt, Jordan, Morocco, Pakistan, and Tunisia in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet